Estudo anatômico do osso temporal de um primata não-humano (Callithrix sp) - Borin, Andrei [UNIFESP] (2008)
The search for experimental (animal) models is essential to the development of clinical studies. AIM: To demonstrate, by means of micro dissection techniques, the anatomical structures of temporal bones from the primate Callithrix sp. STUDY DESIGN: Experimental. METHODS: Dissection of temporal bone structures of Callithrix sp and photographic documentation. RESULTS: We identified the main constituents of the temporal bone (external, medium and inner ear and facial nerve). CONCLUSION: The non-human primate Callithrix sp. is an adequate experimental model for the studies of temporal bone structures given its close anatomical similarities to that found in humans.